Conventional and organic cropping systems at Suitia VI: Insect populations in barley - Helenius, Juha (Agricultural and Food Science, 1990)
In 1988, insects were sampled from tillers and by pitfall trapping in a long-term field experiment consisting of plots of organic and conventional barley. The organic crops suffered from lack of nitrogen and from draught stress, and growth and development were retarded. The stand characteristics were suggested to be the major determinants of the fourfold higher densities of Rhopalosiphum padi(L.) (Horn., Aphididae) and the 50 % lower densities of Frankliniella tenuicornis Uzel (Thys., Thripidae) in the conventional than in the organic barley. The 75 % lower catch rate of Bembidion spp. (Col., Carabidae) in the conventional barley was attributed to lower activity resulting from the more closed canopy and more dense crop. However, the effect of an aphicide applied to the conventional crop was confounded with the true habitat effects. The densities of Coccinella seplempunclata L. (Col., Coccinellidae) were almost three times higher in the conventional than in the organic barley, which in turn was attributed to the higher prey (aphid) densities.